European Union law for the twenty-first century : rethinking the new legal order - Tridimas, Takis; Nebbia Paolisa (Essays in European law., 2004)
This book, to be published in two volumes, is based on the contributions made to the W.G. Hart Workshop 2003. It contains more than forty contributions by leading experts seeking to assess the state of development of EU law some fifty years after the establishment of the Communities and contribute to the current debate on the European Constitution. The first volume concentrates on the theme of European Constitutionalism and analyses the proposed Constitution dealing, among others, with the division of competence between the EU and the Member States, Community legislation, the role of the natio.